Ultrasound-Assisted Extraction of Phenolic Compounds From Brown Rice and Their Antioxidant Activities - Chooklin, Supasit (Agriculture and Natural Resources, 2013)
In this study, the phenolic compounds from brown rice from the Sung Yod area in Phatthalung province, southern Thailand were extracted by ultrasound-assisted extraction. The efﬁ cacy of the brown rice extract in stabilizing reﬁ ned palm oil during accelerated storage was studied. It was found that the total phenolic content obtained by ultrasound-assisted extraction was 15.31% higher than the content obtained by conventional extraction. The optimal conditions using ultrasound-assisted extraction for the brown rice from Sung Yod Phatthalung were 60% volume per volume ethanol concentration, pH 6 and an extraction time of 25 min. The total phenolic acid and 2,2-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity of the brown rice extract under these conditions were 1.30 mg ferulic acid equivalent per gram dry sample and 86.55%, respectively. The oxidation properties (peroxide value, PV and thiobarbituric acid reactive substances, TBARS) of the antioxidant from the brown rice extract in the reﬁ ned palm oil were compared with other synthetic antioxidants—butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT)—at 60 °C. The data obtained indicated that the antioxidant activities of the brown rice extract was higher than those of the control and BHA but lower than for BHT. Moreover, the PV and TBARS values decreased with an increasing concentration of the brown rice extract in reﬁ ned palm oil. The results revealed that the brown rice extract was a potential antioxidant for the stabilization of reﬁ ned palm oil.